Inovação social e desenvolvimento sustentável em redes de agroecologia no semiárido do nordeste do Brasil - Amaral. Inácia Girlene (2024)
Over time, efforts have been made to strengthen family farming to meet the social demands of sustainable agriculture. In this context, practices emerged that are participatory, inclusive, socially mobilized, and with low economic and environmental impact, such as agroecology networks. Thus, this thesis sought to investigate how the relationships between social innovation and sustainable development occur in agroecology networks in the semi-arid region of Northeast Brazil, and is structured in the form of three scientific articles, independent, but intrinsically interrelated. The first article sought to describe the panorama of scientific production on social innovation and sustainable development in the rural environment. This is bibliometric research over the last 10 years, from 2012 to 2023, carried out in the Web of Science database using the keywords and Boolean operators: “social innovation” and “sustainable development” and “rural”, obtaining 58 articles, after reading these articles and using the inclusion and exclusion criteria, only 14 records remained. The results showed that Italy, England and Spain are the countries that play an important role in research involving social innovation, sustainable and rural development, and that there are few publications on the association of these themes in Brazil, which indicates that there is a research gap. It was also observed that the year 2021 had the highest number of publications, but it was publications in 2022 that obtained the highest number of citations in the period investigated. From the analyzed panorama, the following suggestions for future research were observed, such as: the proposition of a theoretical or theoretical-empirical framework covering the themes of this study; research that demonstrates the relationship between social innovation and social development and/or SDGs in rural areas, investigating different socioeconomic activities (permaculture, agroforestry, agroecology, fish farming) in cultures such as quilombola and indigenous cultures in Brazil. The second article aimed to analyze the dimensions of social innovation in agroecology networks in the semi-arid region of Northeast Brazil, based on the theoretical model of Tardif and Harrisson (2005). In this model, social innovation is analyzed taking into account five dimensions: transformation, innovative character, innovation, actors and process. The research is qualitative, exploratory and descriptive in nature, using the multiple case method. The cases studied are two agroecology networks located in the semi-arid region of Northeast Brazil. The analysis technique was content analysis, with the support of Atlas.ti software. From 15 documents compiled in the interviews, a total of 687 citations linked to 73 codes were reached. It was noticed that the two cases have similar characteristics, according to the analysis model by Tardif and Harrisson (2005), such as: having emerged from a crisis, that is, the need to produce healthy and sustainable food for consumption and commercialization. It was also possible to identify that during the historical period since the implementation of the researched networks, until the present time, two common processes occurred: rupture and discontinuity. A period of awareness raising among members is necessary to implement changes in agricultural and economic practices. As a result of these two processes, network members needed to make adaptations in work, production and consumption relations, with member recompositions and new practices in social relations. In the networks researched, some characteristics were detected common to both networks and others, which are unique to a given network. They are present in both networks: governance and work models, mixed economy and the social economy. And social actions: productive arrangements and projects, followed by policies and programs. The level of scale of social innovations in both is local or localized, and the members of the agroecology networks researched articulate with the same types of actors: social, organizational, intermediary and institutional actors. It was possible to detect the presence of the Quebec model in RXX and the development model in RAFTMSP. Social innovations are institutional in both, but in RXX, social innovation is technical and in RAFTMSP, social innovation is organizational. These innovations serve the interests of network members and (collective interests), and are developed cooperatively. Furthermore, it is noted that different degrees of development could be found in the two networks. RXX has product certification, but RAFTMSP does not. However, both present fundamental characteristics of social innovation, according to Tardif and Harrisson (2005). For future research, it is suggested that interviews be carried out with users of the fairs, and an analysis using new approaches to social innovation models, in order to determine whether the final results could be different. The third article sought to understand how social innovation enables sustainable development in agroecology networks in the semi-arid region of Northeast Brazil, based on the model of Mehmood and Parra (2013) and the Sustainable Development Goals (SDGs). With regard to Mehmood and Parra's (2013) model, there are four characteristics of social innovation: satisfaction of needs, changes in social relations, sociopolitical capacity, governance and social/cultural institutions, and three dimensions of sustainable development: social, economic and environmental. And the SDGs featured in social innovation initiatives (agroecology networks) are: 2 – Zero hunger and sustainable agriculture; 5 – Gender equality; 6 – Drinking water and sanitation; 12 – Responsible consumption and production. The research has a qualitative approach, with semi-structured interviews and non-participant observation carried out at RXX and RAFTMSP. It was possible to count a total of 511 citations, 41 codes and seven semantic networks. It was also possible to demonstrate that the relationships between the dimensions of sustainable development (social, economic and environmental) and the characteristics of social innovation (satisfaction of needs; changes in social relations; sociopolitical capacity; governance and social/cultural institutions), were in accordance with the model by Mehmood and Parra (2013). The three dimensions of sustainable development analysis were present, however, in different proportions. The social dimension received a greater number of citations than the economic and environmental dimensions, and was the one with the lowest value. The results of the social dimension of sustainable development were crossed with the characteristics of social innovation, which made it possible to identify the different articulations between members, public and third sector organizations for income generation, food security and sustainability, in addition to the inclusion of women and empowerment, aiming to meet the needs of network members. This fact shows the strengthening of social actors, based on network work. It was possible to identify: the existence of sustainable production and consumption; social entrepreneurship initiatives; decision made in a participatory manner; adaptive management; incentives and strategic investments. In relation to the sustainable development objectives, the presence of the four SDGs was revealed in the analyzed networks, however, in different proportionalities. SDG 2 had the highest number of citations in the two networks analyzed, followed by SDGs 5, 6 and 12, respectively. This research brought a new approach by comparing a social innovation model with the Sustainable Development Goals (SDGs), demonstrating the correlation of this model with the SDGs analyzed in the agroecology networks selected in this work. Differences were observed between the networks, such as the fact that one, RXX, has certification, and the other, RAFTMSP, does not. In this way, we contribute to the formation of a construct about agroecological networks in northeastern Brazil.